Integrated weed management in pulse crops - Kaur, Ramanjit; Ali, Sk Asraful; Sankati, Jhonsonraju; Meena, Dileep (Indian Farming, 2026)
The article explores integrated weed management (IWM) strategies essential for optimising pulse crop production, which is vital for nutritional security and agricultural sustainability. Pulses, known for their high protein content and ability to enrich soil through nitrogen fixation, face significant yield losses due to weed competition, particularly in rainfed conditions. Weeds can cause yield reductions ranging from 30–80%, emphasising the need for effective management practices. It also highlights the importance of understanding weed dynamics, including species composition and growth behaviour, to devise targeted control measures. It advocates a holistic approach that combines manual, mechanical, and chemical methods tailored to specific crops and environmental contexts. Furthermore, the study underscores the necessity of continuous monitoring and adaptive strategies to mitigate weed impacts and enhance crop resilience. By focusing on IWM, pulse productivity can be improved, thereby addressing food security challenges and promoting sustainable agricultural practices in pulse cultivation.